Migraine epidemiology, clinical symptoms, and treatment. (Headache: The Journal of Head & Face Pain, 2005)
Thomas E, Boardman H, Ogden H, Millson D, Croft P. Advice and care for headaches: who seeks it, who gives it? Cephalalgia. 2004;24:740-752.Using data from a cross-sectional survey and a prospective record linkage study, the aims of this study were to (i) determine sources of advice and care for headaches in a population survey of adults and (ii) investigate prospectively the influences of headaches on general practice consultation in a 12-month follow-up of the responders to the population survey. A population-based cross-sectional survey was mailed to 4885 adults (aged>=18 years) with an adjusted response rate of 56% (n= 2662). The main outcome measures of interest were (i) self-report advice and care-seeking in the survey, (ii) consultation with general practitioner for headache and for other conditions in 12-month period subsequent to the survey. Reporting a recent GP consultation for headache was associated with younger age (mean: 46 vs 48 years), female gender (68% vs 60%), and greater headache severity as measured by frequency, pain, and associated disability. The most common sources of advice and care in the past were GPs (27%), opticians (21%), and pharmacists (8%). Consultations for headache were not common in the 12 months following the survey (n= 144); however, those reporting a recent headache were almost four times more likely to consult subsequently with a headache than those who did not (relative risk; 95% CI: 3.7; 1.9, 7.0). Recent reporting of headache was also associated with an increased risk of consulting for mental disorders (1.7; 1.2, 2.6), diseases of the digestive (1.6; 1.1, 2.3) and respiratory system (1.4; 1.1, 1.8), and a decreased risk of consulting for circulatory diseases (0.8; 0.7, 1.0). Only a minority of headache sufferers consults their GP, regardless of severity, with opticians and pharmacists being other important sources of information. Headache appears to have an additional impact upon GP workload through increased rates of consultations for nonheadache conditions among headache sufferers. The interesting findings regarding rates of consultation for digestive and circulatory conditions among headache sufferers may be linked to the use of headache medication.Comment: A fascinating study, in that it not only discusses with whom UK headache patients seek care, but also their comorbid complaints, and ties in the comorbidity and primary headache disorder-Stewart J. Tepper, MD Dowson AJ, Tepper SJ, Baos V, Baudet F, D'Amico D, Kilminster S. Identifying patients who require a change in their current acute migraine treatment: the Migraine Assessment of Current Therapy (Migraine-ACT) questionnaire.Curr Med Res Opin. 2004;20:1125-1135.Background:Currently available measures of the efficacy of acute migraine medications are not frequently used in primary care. They may be too burdensome and complicated for routine use.Objectives:To design and test a new, easy-to-use, four-item assessment tool, the Migraine Assessment of Current Therapy (Migraine-ACT) questionnaire for use by clinicians, to quickly evaluate how a recently prescribed acute medication is working, and to identify patients who require a change of their current acute treatment.Methods:A 27-item Migraine-ACT questionnaire was developed by an international advisory board of headache specialists. Questions were formulated in four domains: headache impact, global assessment of relief, consistency of response, and emotional response. All these are clinically important measures of migraine severity and treatment outcome. All questions were dichotomous and answered by'yes' or'no.' Patients (n= 185) attending secondary care headache clinics who were diagnosed with migraine according to International Headache Society criteria entered a multinational, prospective, observational study to investigate the test-retest reliability and construct validity of the 27-item Migraine-ACT. Patients completed the Migraine-ACT on two occasions, separated by a 1-week interval, and test-retest reliability was assessed by Pearson product moment and Spearman rank measures. Construct validity was assessed by correlating patients' answers to the 27-item Migraine-ACT with those to other questionnaires (individual domains and total scores) conceptually related to it; the Short-Form 36 quality-of-life questionnaire (SF-36), the Migraine Disability Assessment (MIDAS) questionnaire, and the Migraine Therapy Assessment Questionnaire (MTAQ). Discriminatoryt-tests were used to identify the four Migraine-ACT questions (one in each domain) which discriminated best between the domains of the SF36, MIDAS, and MTAQ. These four items constituted the final four-item Migraine-ACT.Results:The test-retest reliability of the 27 Migraine-ACT questions ranged from good to excellent, and correlation coefficients were highly significant for all items. The consistency of reporting the yes and no answers was also excellent. Correlations of Migraine-ACT items with SF-36 and MIDAS items and SF-36, MIDAS, and MTAQ total scores indicated that the following were the most discriminating items, in the respective four domains, and constitute the final Migraine-ACT questionnaire: Consistency of response: Does your migraine medication work consistently, in the majority of your attacks? Global assessment of relief: Does the headache pain disappear within 2 hours? Impact: Are you able to function normally within 2 hours? Emotional response: Are you comfortable enough with your medication to be able to plan your daily activities? The four-item Migraine-ACT was shown to be highly reliable (Spearman/Pearson measurer= 0.82). The individual questions, and the total four-item Migraine-ACT score, showed good correlation with items of the SF-36, MIDAS, and MTAQ questionnaires, particularly with the total MTAQ and SF-36 scores.Conclusions:The four-item Migraine-ACT questionnaire is an assessment tool for use by primary-care physicians to identify patients who require a change in their current acute migraine treatment. It is brief and simple to complete and score, and has demonstrated reliability, accuracy, and simplicity. Migraine-ACT can therefore be recommended for everyday clinical use by clinicians.Comment: Dowson et al have developed a useful tool with which to assess the clinical efficacy of acute migraine treatments. Migraine-ACT does seem to be a simple tool to apply at the coalface of clinical practice in primary care. They report good test-retest reliability with construct validity and have focused in on four key items (representing four domains) from a possible 27 questions. Might this become a new gold standard for use in migraine clinical trials?-David S. Millson, MD Goldstein JA, Massey KD, Kirby S, Gibson M, Hettiarachchi J, Rankin AJ, Jackson NC. Effect of high-dose intravenous eletriptan on coronary artery diameter.Cephalalgia. 2004;24:515-521.The goal of this study was to evaluate the coronary vasoconstrictive effects of high doses of eletriptan compared with a standard dose of sumatriptan. Patients with no clinically significant coronary artery disease were randomized to receive high-dose intravenous eletriptan (n= 24) versus a standard dose of sumatriptan (n= 18; 6 mg subcutaneously) versus placebo (n= 18). Serial angiograms were obtained. The primary noninferiority analysis found equivalence between the mean maximum change in left anterior descending coronary artery diameter for eletriptan,-22%[95% confidence interval (CI)-26,-19], and sumatriptan,-19% (95% CI-22,-16). The change due to placebo was-16% (95% CI-20,-12). No individual cases of clinically significant vasoconstriction were observed. The results confirm that eletriptan has a broad cardiovascular safety margin, with plasma concentrations comparable to three to five times the C(max) of an oral 80-mg dose associated with modest vasoconstriction equivalent to standard therapeutic doses of sumatriptan.Comments: A very reassuring study on the cardiovascular effects of eletriptan at massively supratherapeutic doses, administered intravenously to boot. And the data on sumatriptan are also reassuring. This study, which was suggested by the FDA, is well worth reading in its entirety.-Stewart J. Tepper, MDI agree with Dr. Tepper this is reassuring data for the cardiovascular safety of eletriptan, with subcutaneous sumatriptan as a positive control showing comparable lack of vasoconstriction. Whether this makes the higher dose of eletriptan (80 mg orally) any more acceptable as a starting dose remains to be seen given its drug interaction profile. Unfortunately, clinicians rarely know the'true status' of coronary disease in their patients prior to exposure to a triptan and will still need to apply the cautious template warnings recommended by FDA, which have served us all very well in maintaining the excellent safety profile of the triptans thus far.-David S. Millson, MD Kolodny A, Polis A, Battisti WP, Johnson-Pratt L, Skobieranda F, on behalf of the Rizatriptan Protocol 052 Study Group. Comparison of rizatriptan 5 mg and 10 mg tablets and sumatriptan 25 mg and 50 mg tablets.Cephalalgia. 2004;24:540-546.This randomized, double-blind, two-attack, placebo-controlled, crossover study explored the efficacy and tolerability of rizatriptan 10 mg compared with sumatriptan 50 mg as well as rizatriptan 5 mg compared with sumatriptan 25 mg in the acute treatment of migraine. Following randomization to one of six possible treatment sequences, patients (n= 1447) treated two sequential attacks of moderate or severe intensity separated by at least 5 days. Patients assessed pain severity, migraine-associated symptoms, and functional disability at 0.5, 1, 1.5, and 2 hours post-treatment. Compared with placebo, all treatments were effective. On the primary endpoint of time to pain relief, rizatriptan 10 mg was not statistically different from sumatriptan 50 mg[odds ratio (OR) 1.10,P= .161], and rizatriptan 5 mg was statistically superior to sumatriptan 25 mg (OR 1.22,P= .007). In general, rizatriptan 10 and 5 mg treatment resulted in improvement compared with the corresponding doses of sumatriptan on measures of pain severity, migraine symptoms, and functional disability, and the 5-mg dose reached statistical significance on almost all measures. All treatments were generally well tolerated.Comments: Merck did three rizatriptan-sumatriptan comparison studies. The first two were: Tfelt-Hansen P, Teall J, Rodriguez F, Giacovazzo M, Paz J, Malbecq W, Block GA, Reines SA, Visser WH. Oral rizatriptan versus oral sumatriptan: a direct comparative study in the acute treatment of migraine. Rizatriptan 030 Study Group. Headache. 1998;38:748-755 and Goldstein J, Ryan R, Jiang K, Getson A, Norman B, Block GA, Lines C. Headache. 1998;38:737-747. The current study, completed years ago and always available by request from Merck all these years, is the third. The endpoint of time to pain relief was made difficult to interpret by inclusion as successes patients who obtained pain relief, and then had recurrence in less than 2 hours, which swirled as controversy when these studies were initially presented. In addition, as Dr. Marek Gawel pointed out in a review of these studies (Gawel M, Wiebe S. Evidence-based analysis of a migraine treatment drug comparison trial. Cephalalgia. 2000;20 Suppl 2:33-38), there was an asymmetry in comparison groups, in that patients were required to be rizatriptan, but not sumatriptan naïve, although that bias does not clearly cut one way or another. Nonetheless, symmetry of comparison groups is most important in comparative studies.-Stewart J. Tepper, MDThe delayed publication of this study is a cause for concern. Why has it taken so long to reach the light of day? Given the failure to show robust evidence of superiority for rizatriptan 10 mg versus sumatriptan 50 mg, one is tempted to speculate that commercial factors have influenced dissemination of results which may have been at variance with other marketing messages at time of launch. A recent independent[2004] review of this study published on the internet by the Canadian Evidence based Practice Centre commented: Cook AJ, Roberts DA, Henderson MD, Van Winkle LC, Chastain DC, Hamill-Ruth RJ. Electronic pain questionnaires: a randomized, crossover comparison with paper questionnaires for chronic pain assessment.Pain. 2004;110:310-317.Electronic questionnaires for pain assessment are becoming increasingly popular. There have been no published reports to establish the equivalence or psychometric properties of common pain questionnaires administered via desktop computers. This study compared responses to paper (P) and touch screen electronic (E) versions of the Short-Form McGill Pain Questionnaire (SF-MPQ), and Pain Disability Index (PDI), while examining the role of computer anxiety and experience, and evaluating patient acceptance. In a randomized, crossover design, 189 chronic pain patients completed P and E versions of the SF-MPQ and PDI, and self-ratings of anxiety, experience, relative ease, and preference. Psychometric properties were highly similar for P and E questionnaires. For the SF-MPQ, 60% or more of subjects gave equivalent responses on individual descriptors and PPI scale, with 80% rating within±1 point for an 11-point VAS. Correlations for the SF-MPQ scales ranged from 0.68 to 0.84. For the PDI, 60% or more of subjects responded within±1 point on individual questions, and the total score correlation was 0.67. Comparison of mean difference scores revealed no significant differences between modes for any of the questionnaire items or scores. Anxiety and experience scores showed no significant associations through correlations and high/low comparisons. Although nearly half of the subjects reported no computer training, anxiety ratings were low, and considerably more subjects rated the E questionnaires as easier and preferred. Findings are consistent with test-retest reliability data, and support the validity and acceptance of electronic versions of the SF-MPQ and PDI.Comment: In research, we are increasingly using computers to gather clinical data, but it turns out no one has asked whether they work as well as paper gathering techniques. This study suggests that it is fine to continue the electronic revolution in data collection.-Stewart J. Tepper, MD Pringsheim T, Gooren L. Migraine prevalence in male to female transsexuals on hormone therapy.Neurology. 2004;63:593-594.Migraine prevalence is three times higher in women than men, suggesting that sex hormones may be involved in migraine generation. To further understand the relationship between migraine and sex hormones, we assessed male to female transsexuals (MFTs) using antiandrogens to suppress male sex characteristics and estrogens to induce female sex characteristics for the presence of headache.Compared with The Netherlands' population data, the migraine prevalence of 26% in MFTs is similar to the prevalence of 25% in genetic females and significantly greater than the prevalence of 7.5% in men. Thirty-one percent of patients in the GEM study with migraine had migraine with aura. In our study, 54% of MFTs with migraine or probable migraine headache endorsed visual phenomena before the onset of their headaches in contrast to 2 of 22 (9%) with tension headache. This is interesting given observations on the relationship between high estrogen states and aura. Patients developing migraine aura while using estrogen replacement therapy have been described in which reducing the estrogen dose was associated with the loss of aura. Similarly, when migraine develops for the first time during pregnancy, it is significantly more likely to be migraine with aura. The higher frequency of aura symptoms in MFTs may be related to the high doses of estrogens used.Possible explanations for the prevalence of migraine in MFTs taking hormone therapy include structural differences in the transsexual brain (a female-sized bed nucleus of the stria terminalis has been found in MFTs) that migraine headache is part of the female gender role, or that the stresses of gender reassignment are triggering headache. However, the authors speculate that the prevalence of migraine in MFTs on hormonal therapy is more likely related to the effect of antiandrogen and estrogen therapy on nitric oxide (NO). NO is a known migraine trigger and has a role in mediating nociceptive transmission in migraine. Circulating NO originates mainly from the vascular endothelium. NO levels are influenced by estrogen, which stimulates NO synthesis. Estrogen decreases vascular tone by its effect on NO, which causes endothelium-dependent vasodilation. Antiandrogen treatment in MFTs increases circulating NO levels by 72%. Estrogen treatment in MFTs has been shown to improve endothelial (NO)-dependent vasodilation in the forearm resistance circulation. These physiologic changes in circulating NO and endothelial-dependent vasodilation related to the use of estrogens and antiandrogens may contribute to the generation of migraine in this unique group of patients.In conclusion, MFTs taking hormonal therapy have similar rates of migraine as genetic females. Because this is a small and uncontrolled study, follow-up evaluation of this result is recommended with established baseline headache histories and examination by a neurologist to confirm the diagnosis. Lipton RB, Bigal ME, Steiner TJ, Silberstein SB, Olesen J. Classification of primary headaches.Neurology.2004;63:427-435.Given the range of disorders that produce headache, a systematic approach to classification and diagnosis is an essential prelude to clinical management. For the last 15 years, the diagnostic criteria of the International Headache Society (IHS) have been the accepted standard. The second edition ofThe International Classification of Headache Disorders(January 2004) reflects our improved understanding of some disorders and the identification of new disorders. Neurologists who treat headache should become familiar with the revised criteria. Like its predecessor, the second edition of the IHS classification separates headache into primary and secondary disorders. The four categories of primary headaches include migraine, tension-type headache, cluster headache and other trigeminal autonomic cephalalgias, and other primary headaches. There are eight categories of secondary headache. Important changes in the second edition include a restructuring of these criteria for migraine, a new subclassification of tension-type headache, introduction of the concept of trigeminal autonomic cephalalgias, and addition of previously unclassified primary headaches. Several disorders were eliminated or reclassified. In this article, the authors present an overview of the revised IHS classification, highlighting the primary headache disorders and their diagnostic criteria. They conclude by presenting an approach to headache diagnosis based upon these criteria.Comment: A worthwhile stop on your way to perusing the full International Classification of Headache Disorders II available in Cephalalgia 2004;24(Supplement 1).-Stewart J. Tepper, MD Afridi SK, Kaube H, Goadsby PJ. Glyceryl trinitrate triggers premonitory symptoms in migraineurs.Pain. 2004;110(3):675-680.Studying attacks of migraine is considerably hampered by its fundamentally episodic nature. Developing approaches to triggering migraine reliably is important for advancing understanding of the disorder by facilitating its study. Based on the work of the Copenhagen Group, we administered an intravenous infusion of 0.5[mu]g/kg/min glyceryl trinitrate (GTN) to 44 migraineurs, 23 migraine without aura, 21 migraine with aura, and to 12 healthy controls. We sought to characterize the GTN-induced migraine in terms of the clinical features of the attacks and reproducibility of triggering, and included a nonmigraine control group for the purpose of comparing any effects to exclude an ordering effect. Of the 44 patients administered GTN, 33 had a migraine attack fulfilling International Headache Society criteria. Thirty-two attacks were of migraine without aura and one of migraine with aura. Twelve patients described typical premonitory symptoms, which have not been previously documented with GTN-induced migraine. A repeat attack was triggered in all subjects but one. In one case, a visual aura was also triggered both times. Our study shows that GTN-induced triggering is common in our patients, and remarkably reproducible. The data will facilitate the use of the GTN model in studies requiring extensive planning, such as brain imaging, or where preventive questions are at issue. We also report the first patient with a reproducible GTN-triggered migraine with aura.Comment: This study is further confirmation of Professor Jes Olesen's theory that nitric oxide is the final common pathway in migraine, and that GTN can serve as a vehicle for its production, resulting in delayed migraine. What is new and exciting is the description of triggering of premonitory symptoms, and of migraine with aura.-Stewart J. Tepper, MD